C-doped Bi3O4X nanosheets with self-induced internal electric fields for pyrene degradation: Effects of carbon and halogen element type on photocatalytic activity - Yanyu Song; Weiyu He; Xianbo Sun; Juying Lei; Long D. Nghiem; Duan, Jun; Liu, Wen; Yongdi Liu; Cai, Zhengqing (Separation and Purification Technology, 2023)
A series of C-doped Bi3O4X (X = Cl, Br, I) photocatalysts with layer-stacked structure was synthesized using glucose as carbon source, and the carbon doping and halogen species on harvesting broader solar spectrum and promoting charge carrier separation were systematically investigated. For pyrene photolysis, the photodegradation rate of pristine materials followed the order of Bi3O4I > Bi3O4Br > Bi3O4Cl, which was attributed to the difference in electronegativity of the halogen elements. The doped carbon boosted photocatalytic performance and the optimal C/Bi3O4I achieved 100% pyrene removal within 20 min, which primarily benefited from the dramatic improvement of the internal electric field (IEF). The improved IEF further increased the separation and transfer efficiency of photogenerated charge carriers. XRD and XPS characterizations confirmed that the doped carbon implanted into the lattice of [X] layers, and mainly affected the X np states. The X np orbitals contributed to the valence band (VB) of Bi3O4X, thus the local occupied states induced by doped carbon formed above VB and significantly decreased the VB potential. Meanwhile, the doped carbon narrowed the band gap and greatly improved visible light utilization. The O2−, h+ and OH were identified as dominant active species for pyrene degradation, and the generation rate of O2− and OH was further measured by the probe technique. Moreover, the photodegradation pathways of pyrene were proposed and the ecotoxicity of intermediates was assessed. This study reveals the effect of halogen species on photocatalytic activity and provides guidance for enhancing IEF by doping inorganic element.
Keywords: Carbon doping; Halogen species; Internal electric field; Photocatalysis